Estimasi Ripitabilitas Produksi Telur Puyuh Berdasarkan Bobot Telur Melalui Tingkat Efisiensi Pakan - Nova, Dini; Bilyaro, Woki; Faridatus Soleha, Meilita; Salsa Bella Mahdika Putri, Syifa (Program Studi Biologi, Fakultas Sains dan Teknologi, UNIPAR JEMBER, 2024)
Quail is one type of poultry that gained popularity in Indonesia. It is proven by the fact that many people are interested in raising quail and the number of people eating quail products is increasing, both eggs and meat. The advantages of quails are that they are easy to care for, produce quickly and have a high immunity to disease. Quail rearing research aims to determine the ripitability value of the calculation of egg weight and quail egg index. The study was divided into several groups and then assigned to raise quail every day in turn. The first thing to do in quail rearing is to weigh the body weight of the quail every week and then recorded, then measure the length of the shank using a caliper and expressed in mm. Feeding was done every morning, afternoon, and evening in the first week with a total dose of 20 grams/day. Another factor that affects the size of the egg and thus the ripitability value is the feed. The feed consumption rate of quails is influenced by the energy level and palatability of feed in quails. The feed consumption rate of quails was 109.69-135.59 g/head/week. The average feed consumption of quails in the study ranged from 127.12-165.15 g/head/week. Based on calculations from the recapitulation of data obtained during quail rearing, it is known that the ripitability value of egg weight and quail egg index is included in the low category.